2015
DOI: 10.1007/s00251-015-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex class IIB polymorphism in an ancient Spanish breed

Abstract: Genes from the Major Histocompatibility Complex class II region are involved in the presentation of antigens. Therefore, they have the key role in regulating the immune response and in the resistance to infections. We investigated the Major Histocompatibility Complex class IIB genes, DRB and DQB, in Churra sheep, one of the most important indigenous breeds of Spain. These genes are among the most polymorphic in the mammalian genome. Furthermore, often different numbers of class IIB genes per haplotype exist, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…It is worth noting that homozygosity at the DRB1 locus does not mean that the animal is always homozygous across the MHC class II region. The ovine MHC class II region includes a range of polymorphic DQ loci [38] and a number of studies have identified diversity at the duplicated DQA and DQB loci linked with identical DRB1 alleles [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that homozygosity at the DRB1 locus does not mean that the animal is always homozygous across the MHC class II region. The ovine MHC class II region includes a range of polymorphic DQ loci [38] and a number of studies have identified diversity at the duplicated DQA and DQB loci linked with identical DRB1 alleles [4].…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the utility of the method, we sought to determine whether genomic DNA could be obtained from archived plasma samples, and tested if alleles of the Ovar-MHC class II locus could be amplified from these samples. We focussed on the DRB1 locus which is the most highly polymorphic MHC class II locus of domestic sheep (Ovis aries) [4,5]. The MHC class II genes encode dimeric cell surface glycoproteins that present peptides to the adaptive immune system for recognition by CD4+ T cell receptors [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region was highlighted is a meta‐analysis of 3 diverse sheep breeds (Scottish Blackface, Sarda × Lacaune and Martinik Black‐Belly × Romane) using RHM methodologies with a 100‐SNP window . The most studied gene of the MHC complex is DRB1 . Conversely, the highly polymorphic nature of this region (over 80 known alleles) and the significant role that it plays in the spectrum of immune‐mediated genetic disease are likely to make it difficult to identify SNPs that will be useful for selecting for GIN resistance without affecting susceptibility to other traits .…”
Section: Genetic/genomic Markers Of Resistance To Gin Infectionmentioning
confidence: 99%
“…105 The most studied gene of the MHC complex is DRB1. 61,79,107,121 Conversely, the highly polymorphic nature of this region (over 80 known alleles) and the significant role that it plays in the spectrum of immune-mediated genetic disease are likely to make it difficult to identify SNPs that will be useful for selecting for GIN resistance without affecting susceptibility to other traits. 114 Many studies have yielded an association between this chromosomal region and parasite resistance traits, but several more have not.…”
Section: Chromosomal Regions Important For Resistance To Gin Infectionmentioning
confidence: 99%